Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4161/rna.29356
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNAs that specifically target tumor suppressive KLF6-FL rather than oncogenic KLF6-SV1 isoform

Abstract: Waye (2014) Identification of miRNAs that specifically target tumor suppressive KLF6-FL rather than oncogenic KLF6-SV1 isoform, RNA Biology, 11:7,[845][846][847][848][849][850][851][852][853][854]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 58 publications
0
43
0
Order By: Relevance
“…It has been shown that miR-1301 expression was downregulated in HepG2 cells and that this miRNA mediated cell apoptosis via Wnt/β-catenin signaling by targeting B-cell CLL/lymphoma 9 protein (BCL9) [60,61]. However, Liang's study revealed that miR-1301 negatively regulated tumor suppressor full-length Kruppel-like factor 6 (KLF6-FL) and induced cellular migration and angiogenesis [62]. In prostate cancer cells, this miRNA promoted proliferation by inhibiting PPP2R2C and facilitated the expansion of cancer stem cells by suppressing GSK3β and SFRP1 [63,64].…”
Section: Discussionmentioning
confidence: 90%
“…It has been shown that miR-1301 expression was downregulated in HepG2 cells and that this miRNA mediated cell apoptosis via Wnt/β-catenin signaling by targeting B-cell CLL/lymphoma 9 protein (BCL9) [60,61]. However, Liang's study revealed that miR-1301 negatively regulated tumor suppressor full-length Kruppel-like factor 6 (KLF6-FL) and induced cellular migration and angiogenesis [62]. In prostate cancer cells, this miRNA promoted proliferation by inhibiting PPP2R2C and facilitated the expansion of cancer stem cells by suppressing GSK3β and SFRP1 [63,64].…”
Section: Discussionmentioning
confidence: 90%
“…MiRNAs belong to a cluster of functionally active non-coding RNAs and exert their function by annealing to target sites located in the mRNA transcripts, with which they form the RNA-induced silencing complex (RISC) and subsequently trigger mRNA degradation or translational inhibition [ 21 23 ]. It's well documented that aberrant miRNA expression profiles have been causally connected to epithelial to mesenchymal transition and tumor progression [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 Functionally, stable expression of KLF6 inhibits cell proliferation, migration, and angiogenesis of HCC, 13 suggesting that KLF6 may play a dual role in the tumorigenesis of some malignancies. In the present study, we found that KLF6 was lowly expressed in HCC tissues and was negatively correlated with the liver cirrhosis and LVSI in HCC patients, indicating that loss of KLF6 might be related with the progression of HCC.…”
Section: Discussionmentioning
confidence: 99%